Analisis Kepuasan Wisatawan Di Daya Tarik Bali Bird Park Melalui Laman “Google Review” - Handayani, Putu Marta; Suryasih, Ida Ayu (JURNAL DESTINASI PARIWISATA, 2023)
Bali Bird Park is an artificial tourist attraction located in Singapadu village, Gianyar which focuses on conservation, recreation and education areas. This research was intended to find out what factors influence the tourist satisfaction in visiting tours made by Bali Bird Park. The design of this study used a review observation survey method and cluster random sampling through the Google Reviews page as the data collection tool involving 50 tourist reviewers who had visited the Bali Bird Park. The collected data were analyzed using descriptive analysis qualitative. This study aims to understand visitor views, improve service quality, and improve the reputation of the tourism industry on the Google Review of the Bali Bird Park tourist attraction. The results of this study indicated that the main factors that influence tourist satisfaction in visiting the Bali Bird Park are tourist attraction and tourism destination attractiveness. In addition, it is also influenced by several variables including satisfaction with easy-to-reach accessibility, tourism facilities, and visiting rates. Keywords: Satisfaction, Tourist, Google Review, Bali Bird Park